A review of noble gas geochemistry in natural gas from sedimentary basins in China. (1st May 2023) - Chen, Biying; Liu, Yi; Fang, Lujia; Xu, Sheng; Stuart, Finlay M.; Liu, Congqiang
Graphical abstract: Highlights: The work systematically compiles noble gas data in natural gas from sedimentary basins in China. The application of noble gases is constrained to trace fluid origins and reflect regional tectonic settings. Using noble gases to understand hydrocarbon accumulation and guide resource exploration needs more attention. Noble gases in CO2 fields from eastern China show great potential in exploring geological CO2 sequestration. Abstract: Natural gas has a critical place in global fuel energy mix, not least as a transition to low carbon emissions. It plays an important role in national energy production and consumption in China. The complex transport and interaction processes of fluids at reservoirs are key to the formation of a gas reserve. The abundance and isotopic composition of noble gases have proved to be a powerful tracer of physical processes and interaction history of reservoir fluids. Noble gas studies of natural gas systems in China started in the 1970s and recent studies are leading examples of the application of the technique. Here we present the first systematic compilation of published noble gas data of natural gases from sedimentary basins in China and review their application and implications to date. Helium isotopes are most commonly used to trace fluid origins, providing a constraint on regional tectonic settings. Argon isotopes are used to indicate the source rock age, the reliability of which, however, is assessed in the work. Noble gases are increasingly used to determine gas accumulation history, estimate oil/gas reserves and evaluate sweet spots for oil/gas exploration. This review points out the limited application of noble gases in sedimentary basins and the slow development of analytical techniques for noble gas isotopes in China. The potential for noble gas studies in exploring the characteristics of local crust and mantle is discussed, as is the identification of the potential for future study of geothermal systems, enhanced oil/coalbed methane recovery and geological CO2 sequestration.